2006
DOI: 10.1021/bi051593z
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Protein Phosphatase 2A to the L-Type Calcium Channel Cav1.2 next to Ser1928, Its Main PKA Site, Is Critical for Ser1928 Dephosphorylation

Abstract: The cAMP-dependent protein kinase (PKA) controls a large number of cellular functions. One critical PKA substrate in the brain and heart is the L-type Ca(2+) channel Ca(v)1.2, the activity of which is upregulated by PKA. The main PKA phosphorylation site is serine 1928 in the central pore forming alpha(1)1.2 subunit of Ca(v)1.2. PKA is bound to Ca(v)1.2 within a macromolecular signaling complex consisting of the beta(2) adrenergic receptor, trimeric G(s) protein, and adenylyl cyclase for fast, localized, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
111
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 81 publications
2
111
0
Order By: Relevance
“…There is little information on the particular domains of the PP2A holoenzyme trimeric complex that define such subcellular targeting. Although yeast two-hybrid studies have shown that PP2A/c, and not B, subunits interact directly with the ā£ 1 -subunit of the L-type Ca 2Ļ© channel (11,22), a more common targeting motif is seen in ryanodine receptor/PP2A interactions where PP2A is tethered through a B-targeting subunit, PR130 (43,65). Yeast two-hybrid studies have defined distinct binding activities for B56 subunits although the sites have not been defined with precision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little information on the particular domains of the PP2A holoenzyme trimeric complex that define such subcellular targeting. Although yeast two-hybrid studies have shown that PP2A/c, and not B, subunits interact directly with the ā£ 1 -subunit of the L-type Ca 2Ļ© channel (11,22), a more common targeting motif is seen in ryanodine receptor/PP2A interactions where PP2A is tethered through a B-targeting subunit, PR130 (43,65). Yeast two-hybrid studies have defined distinct binding activities for B56 subunits although the sites have not been defined with precision.…”
Section: Discussionmentioning
confidence: 99%
“…In heart, PP2A function is necessary for normal excitation-contraction coupling, and PP2A levels are altered in heart failure (1,57,58). Numerous studies have suggested that PP2A activity is associated with critical cardiac receptors, ion channels, and transporters including ā¤-adrenergic receptor (10,12,22), L-type Ca 2Ļ© -channels (11,22), ryanodine receptor (43), Na/Ca exchanger (70), inositol 1,4,5-trisphosphate [Ins(1,4,5)P 3 ] receptor (13), and Na/K ATPase (35).…”
mentioning
confidence: 99%
“…Polyclonal antibodies were affinity purified as described [1]. The affinity and specificity of the antibodies were tested by immunoprecipitation and immunoblotting of HA-tagged PP2A B' subunits expressed in HEK cells [1] and brain lysate [52]. This pan-specific antibody specifically detects the HA-tagged forms expressed in HEK cells as well as several endogenous B' subunit isotypes ranging from 52-72 kDa present in brain lysate.…”
Section: Immunogen Preparation Antibody Production Affinity Purificmentioning
confidence: 99%
“…Basically, doubling of the exposure time has to lead to a doubling of the signal as we published earlier (41,42). Signals were scanned using an Epson Perfection 4180 Photo flatbed scanner and EPSONscan software (42).…”
mentioning
confidence: 99%
“…Basically, doubling of the exposure time has to lead to a doubling of the signal as we published earlier (41,42). Signals were scanned using an Epson Perfection 4180 Photo flatbed scanner and EPSONscan software (42). To ensure that signals were comparable between different films and not distorted by using non-linear contrast functions, neither autocontrast nor any other manipulations of contrast such as non-linear transformation were applied throughout the whole procedure.…”
mentioning
confidence: 99%